Living martyrs in late antiquity and beyond: surviving martyrdom - Fruchtman, Diane Shane (Routledge studies in the early Christian world, 2023)
Introduction: Rethinking martyrdom -- Destabilizing death : Prudentius's Peristephanon -- Modeling the living martyr : witness in and through poetry -- Paulinus of Nola and the living martyr -- Making martyrs in the Nolan countryside -- Non Poena Sed Causa -- Augustine and the life of martyrdom -- Conclusion: Surviving martyrdom : history, historiography, and power.